Implementasi Aplikasi E-Tilang Dalam Menegakkan Hukum Bagi Pelanggar Lalu Lintas - Sabathini, Siagiancindy (Indonesian Journal of Police Studies, 2017)
Research is motivated by the era of globalization which affects the level of community mobility. Traffic violations which are increasing every year, the use of tickets in enforcing the law for traffic violators and changes in the traffic mechanism in traffic unit of Polres Garut. Based on these things, the author examines the application of E-ticketing in enforcing the law for traffic violators in Polres Garut. The author uses research literature and conceptual literature. The theories and concepts used are management theory, innovation diffusion theory, application concepts, E-ticketing concepts, the concept of law enforcement, the concept of traffic violations. This study uses a qualitative approach, with field research methods. Data collection techniques used were interviews, observation and document study. Technical analysis of data through data reduction, data display and conclusion drawing. The author conducts research to analyze the general description of E-Tilang applications, the implementation of the use of E-Tilang applications in enforcing the law and the factors that influence the application of E-Tilang applications by traffic unit of Polres Garut. A change in the ticketing mechanism at the traffic unit of Polres Garut, from a conventional ticket to an E-Ticket. Even so, the application of the E-Ticket application is not in accordance with the SOP. Many people do not know and understand the application of E-Traffic. E-ticket is considered more complicated and the fines applied are more expensive. The lack of socialization by the Garut Regional Police Traffic Unit regarding applications and training related to E-Traffic has not been received by all members of the traffic unit of Polres Garut. It is recommended that in-depth education and training on E-ticketing be given to all members of the traffic unit of Polres Garut and regular outreach to the Garut community, evaluation of the application of the E-ticket application and the provision of budgets related to quotas and mobile phones in the enforcement of traffic violations in Polres Garut.